Digital Religiosity: Challenges in Strengthening the Islamic Character of Generation Alpha on Social Media - Siti Sundari; Wahyu Hidayat; Rachmat Rifky Septian; Hairiyanto Hairiyanto (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2026)
Background: Generation Alpha (born after 2010) has grown up in an era where digital technology and social media are integrated into nearly every aspect of life, giving rise to the concept of "digital religiosity." However, the massive flow of information on social media creates major challenges, including moral degradation, exposure to radical content, and the shallowing of religious understanding caused by social media algorithms. This study aims to analyze the challenges of strengthening the Islamic character of Generation Alpha on social media and formulate an adaptive conceptual strategy for parents and educators.Method: This study employs a descriptive-analytical qualitative method based on library research. Data were collected from reputable books and journals published during the last ten years (2016-2026). The analysis focuses on identifying key challenges and formulating strategic responses to address the unique religious and moral needs of Generation Alpha in the digital environment.Results: The findings show that Generation Alpha's digital religiosity tends to be superficial and vulnerable to value distortion due to limited religious digital literacy. The state of the art of this study expands the field of digital sociology of religion, which previously focused largely on Generation Z, by shifting attention to Generation Alpha as a fully hyper-connected cohort. The novelty of this research lies in the formulation of the "Cyber-Akhlak" model, an integrative framework that combines independent algorithmic supervision with digital role modeling.Conclusion: Strengthening Islamic character in the digital era can no longer rely solely on conventional doctrinal methods, but must be based on collaboration within a healthy digital ecosystem. Recommendations are addressed to policymakers, educators, and parents to develop a family-based Islamic digital literacy curriculum.